1975
DOI: 10.1139/v75-325
|View full text |Cite
|
Sign up to set email alerts
|

The Photolysis of Matrix Isolated cis-Thionylimide. 1. The Identification and Infrared Spectra of cis-HOSN, HSNO, and SNO

Abstract: PETER 0 . TCHIR and RICHARD D. SPRATLEY. Can. J . Chem. 53,2318Chem. 53, (1975. cis-HNSO has been photolyzed in argon matrices using a medium pressure mercury lamp. Examination of the infrared spectra has revealed the presence of four photolysis products. With the aid of isotopic substitution these species have been identfied as cis-HOSN, cis-HSNO, trans-HSNO, and SNO, all previously unknown. Assignments have been made for a11 four products and force fields calculated for cis-HOSN and trans-HSNO. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 2 publications
(2 reference statements)
1
20
0
Order By: Relevance
“…Even so, sulfur is one of the eleven elements that appear on the astrochemist's periodic table (McCall 2006), and is present in many known interstellar molecules (Penzias et al 1971;Gottlieb & Ball 1973;Fock & McAllister 1982;McCarthy & Thaddeus 2001;Tercero et al 2010;Neufeld et al 2012;Gratier et al 2016). It is necessary to life as we know it, gives rise to novel chemistry in extreme environments like hot springs and black smokers on Earth, heavily influences the atmospheric chemistry of Venus (Krasnopolsky 2007(Krasnopolsky , 2012 as well as the surface chemistry of Io, and is present in various terrestrial pollutants (Tchir & Spratley 1975;Hawkins & Downs 1984). Consequently, sulfur cannot be neglected for astrochemical analysis, and an understanding for its importance in the chemistry of space has been continually growing since various molecular sulfur detections began in the 1970s (Morris et al 1975;Henkel et al 1983;Johansson et al 1984;Ziurys et al 1984;Cernicharo et al 1987Cernicharo et al , 2000Kaifu et al 1987;Saito et al 1987;Turner 1987Turner , 1992Kahane et al 1988;Martín-Pintado et al 1992;Boyle et al 1994;Turner et al 1998;Schilke et al 2001Schilke et al , 2003Mauersberger et al 2004;Sakai et al 2007;Finney et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, sulfur is one of the eleven elements that appear on the astrochemist's periodic table (McCall 2006), and is present in many known interstellar molecules (Penzias et al 1971;Gottlieb & Ball 1973;Fock & McAllister 1982;McCarthy & Thaddeus 2001;Tercero et al 2010;Neufeld et al 2012;Gratier et al 2016). It is necessary to life as we know it, gives rise to novel chemistry in extreme environments like hot springs and black smokers on Earth, heavily influences the atmospheric chemistry of Venus (Krasnopolsky 2007(Krasnopolsky , 2012 as well as the surface chemistry of Io, and is present in various terrestrial pollutants (Tchir & Spratley 1975;Hawkins & Downs 1984). Consequently, sulfur cannot be neglected for astrochemical analysis, and an understanding for its importance in the chemistry of space has been continually growing since various molecular sulfur detections began in the 1970s (Morris et al 1975;Henkel et al 1983;Johansson et al 1984;Ziurys et al 1984;Cernicharo et al 1987Cernicharo et al , 2000Kaifu et al 1987;Saito et al 1987;Turner 1987Turner , 1992Kahane et al 1988;Martín-Pintado et al 1992;Boyle et al 1994;Turner et al 1998;Schilke et al 2001Schilke et al , 2003Mauersberger et al 2004;Sakai et al 2007;Finney et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical studies of HNSO in matrices have detected absorption lines due to residual water vapor in the spectrometer. the formation of NSO, SNO, and various HNSO isomers (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…13 18 A common theme of these studies is that SNO or NSO were observed as a decomposition product of other S, N, and O containing molecules. Early assignments of the stretching vibrational frequencies of SNO and NSO came from Tchir and Sprately, 13,14 where isomers of HSNO were formed in an argon matrix and subsequent UV irradiation yielded several vibrational absorption peaks. Some of these peaks were then attributed to either SNO or NSO, resulting in an assignment of the NO stretch and SNO bend vibrational frequencies of SNO 13 and the SO stretching frequency for NSO.…”
Section: Introductionmentioning
confidence: 99%
“…Early assignments of the stretching vibrational frequencies of SNO and NSO came from Tchir and Sprately, 13,14 where isomers of HSNO were formed in an argon matrix and subsequent UV irradiation yielded several vibrational absorption peaks. Some of these peaks were then attributed to either SNO or NSO, resulting in an assignment of the NO stretch and SNO bend vibrational frequencies of SNO 13 and the SO stretching frequency for NSO. 14 It was later suggested that the initial assignments of SNO vibrational frequencies were better matched to the SN and NO stretches, rather than the NO stretch and SNO bend.…”
Section: Introductionmentioning
confidence: 99%